Observation of transverse coherent backscattering in disordered photonic structures - Boguslawski, Martin (2018)
Coherent backscattering, also referred to as weak localization, is an exciting multidisciplinary phenomenon that appears in disordered systems of multiple coherent-wave scattering. Providing proper scattering conditions in (2 + 1) dimensional randomized photonic systems, we optically implement, observe, and analyse transverse coherent backscattering. Ensembles of disordered wave-guide structures are prepared by random-intensity nondiffracting writing entities according to the beam’s intensity distribution. The structure size of the induced potentials naturally define an effective mobility edge, and thus, we identify a crucial impact of the plane probe waves’ spatial frequency on the strength and shape of the spectral coherent backscattering signal. We additionally observe transverse elastic scattering as a precursor of weak localization. To testify the coherent character as a fundamental condition for coherent backscattering, we propose a scheme to continuously reduce the spatial coherence of the probe beam which directly reduces the degree of localization and coherent backscattering. With our experiments, we propose a testing platform that allows comprehensive examination of coherent backscattering with a broad set of preparation parameters and under uncritical laboratory conditions. Our results are directly transferable to more complex systems of disordered wave potentials, not being restricted to photonic systems.